2017
DOI: 10.1080/02673843.2017.1389758
|View full text |Cite
|
Sign up to set email alerts
|

Family and school social capital, school burnout and academic achievement: a multilevel longitudinal analysis among Finnish pupils

Abstract: Research on the associations between family and school social capital, school burnout and academic achievement in adolescence is scarce and the results are inconclusive. We examined if family and school social capital at the age of 13 predicts lower school burnout and better academic achievement when graduating at the age of 16. Using data from 4467 Finnish adolescents from 117 schools and 444 classes a three-level multilevel analysis was executed. School social capital, the positive and supportive relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 56 publications
3
34
0
3
Order By: Relevance
“…Despite the lack of causality between the received feedback and pupils' perceptions, it is notable that perceived intrinsic motivation and the relationship with teachers were weakest for pupils receiving negative feedback or no feedback at all when considering the effect sizes. Therefore, this study supports the earlier findings that not all pupils perceive themselves as being treated similarly at school (Linnakylä & Malin, 2008), and school plays an important role in building academic well-being (Lindfors et al, 2017).…”
Section: Technology-enhanced Feedback Connections To Learning and Acasupporting
confidence: 91%
See 1 more Smart Citation
“…Despite the lack of causality between the received feedback and pupils' perceptions, it is notable that perceived intrinsic motivation and the relationship with teachers were weakest for pupils receiving negative feedback or no feedback at all when considering the effect sizes. Therefore, this study supports the earlier findings that not all pupils perceive themselves as being treated similarly at school (Linnakylä & Malin, 2008), and school plays an important role in building academic well-being (Lindfors et al, 2017).…”
Section: Technology-enhanced Feedback Connections To Learning and Acasupporting
confidence: 91%
“…By clustering the PISA data, Linnakylä and Malin (2008) found that while some pupils are highly engaged, almost one-third perceived teachers as unsupportive and school as less important, and hence it is worth studying whether technology-enhanced feedback is connected to the relationship with teachers. Furthermore, it has been observed that in Finland, relationships with teachers at school are 4 / 15 stronger predictors of academic well-being than parental support (Lindfors, Minkkinen, Rimpelä, & Hotulainen, 2017).…”
Section: Feedback and Academic Well-beingmentioning
confidence: 99%
“…The significant proportion of the variance attributable to differences between schools suggests that the role of student composition and contextual factors cannot be ignored in the complex relationship between health and educational aspirations [34, 41].…”
Section: Discussionmentioning
confidence: 99%
“…The study [23] showed that social competence is essential for finding an association between school engagement and students' well-being. In research on social capital and school exhaustion, it was shown that school social capital, as well as positive and supportive relationships between students and teachers, may produce less school exhaustion and positively influence academic performance [24].…”
Section: School Burnout Preventionmentioning
confidence: 99%